Development of a Village Life Pharmacy Park and Health Counseling for Posyandu Cadres in Semambung Village, Gedangan District, Sidoarjo Regency: Pembangunan Taman Apotek Hidup Desa Serta Penyuluhan Kesehatan Pada Kader Posyandu Desa Semambung, Kecamatan Gedangan, Kabupaten Sidoarjo - Hanif, Aisha; Rahmah, Cut Ami (Universitas Muhammadiyah Sidoarjo, 2022)
During this pandemic, it isn’t an easy thing to continue to survive in various fields, including maintaining physical and spiritual health. Semambung is a village with a strategic location as a wetland for the construction of government and private office buildings, as well as the location of UMKM that were built from various businesses for business opportunities, causing a lack of water absorption so that it is prone to flooding due to reduced infiltration land. Floods have the potential to cause many diseases, especially in toddlers, who are often sick are more at risk of stunting, which is a condition of body and brain growth failure in toddlers due to chronic malnutrition. Semambung-Gedangan-Sidoarjo still has a stunting prevalence. Utilization of empty yard land into a Living Pharmacy Garden equipped with biopore holes as rainwater absorption is one of the prevention efforts to overcome family malnutrition and flood prevention. The purpose of this service activity is to increase the knowledge and skills of cadres in utilizing the land around the house into a private Living Pharmacy Garden and making biopore holes. Activities related to making biopore holes, types of Moringa leaf plants, nutritional content, and their benefits for meeting nutritional needs and increasing the quality and quantity of breast milk. Moringa leaves have many benefits for treating skin diseases, shortness of breath, cancer, dental infections, gingivitis, hypertension, diabetes as well as improving nutrition and stunting. Furthermore, a demonstration of making Moringa Cendol as an innovative nutritious drink that can be used as a PMT in the routine activities of Posyandu for toddlers in Semambung was carried out. Posyandu cadres are expected to be able to optimally utilize the Village Life Pharmacy Garden and biopore holes, applying them to their respective home gardens.